Models and Algorithms of Automata Theory for the Control of an Aircraft Group - Rezchikov, A. F.; Kushnikov, V. A.; Ivashchenko, V. A.; Bogomolov, A. S.; Filimonyuk, L. Yu (Automation and remote control, 2018)
We develop models and algorithms to control the process of landing aircraft under uncertainty of their positions in space caused by unfavorable, unforeseen external influences. As the objective function we consider the execution time of the dispatcher’s commands, and as constraints we introduce requirements for the safety of aircraft. Based on the developed formalism of generalized synchronization of linear automata, we develop an approach that makes it possible to reduce this problem to an integer linear programming problem. We consider an example of the use of the developed models and methods for controlling the aircraft landing process.